Building Nutritious Food Baskets An integrated advocacy and capacity strengthening approach - International Potato Center (2017)
The Building Nutritious Food Baskets (BNFB) project completed the situation analysis reports and advocacy strategies and strengthened the capacity of 50 advocates and champions in Nigeria, Tanzania and at the regional level to engage policy makers and raise new investment for biofortified crops. BNFB helped incentivize and build the capacity of national and community supportive agencies including training institutions, non-governmental organizations, seed companies and agro-processing companies as well as individuals. In total, 577 (263 female) change agents (283 Nigerians and 294 Tanzanians) have been equipped with the capacity to design and implement gender sensitive projects on orange-fleshed sweetpotato, pro-vitamin maize, and high-iron beans.